15 Katlı Betonarme Bir Binanın Deprem Performansının Zaman Tanım Alanında Doğrusal Elastik Olmayan Hesap Yöntemi İle Belirlenmesi - Çoban, Pınar (Fen Bilimleri Enstitüsü, 2015)
Yapı sistemlerinin dış yükler ve deprem etkileri altındaki davranışlarının incelenmesinde doğrusal ve doğrusal olmayan hesap yöntemleri kullanılabilmektedir.  Doğrusal teoriye göre hesapta, malzemenin doğrusal elastik ve yer değiştirmelerin çok küçük olduğu varsayılmakta, yönetmeliklerde yer alan doğrusal hesap yöntemleri uygulanarak yapı sisteminin analizi ve boyutlandırması yapılmaktadır. Doğrusal olmayan hesapta ise, malzemelerin doğrusal-elastik sınırın ötesindeki davranışı hesaba katılmakta ve yer değiştirmelerin çok  küçük olmadıkları göz önünde tutulmaktadır. Son yıllarda yaşadığımız şiddetli depremler ve bu depremlerin sebep olduğu can ve mal kayıpları depreme dayanıklı yapı tasarımının önemini arttırmıştır. Bu konu hakkında hem yurt dışında hem yurt içindeki akademisyenler tarafından araştırmalar yapılmaya devam etmektedir. Bu yapılan araştırmalarla birlikte bilgisayar, teknoloji, malzeme ve imalat sektöründeki gelişmelere paralel olarak Deprem Bölgelerinde Yapılacak Yapılar Hakkında Yönetmelik kapsamına Mevcut Binaların Değerlendirilmesi ve Güçlendirilmesi için Bölüm 7 eklenmiş ve 06.03.2007 tarihli 26454 numaralı resmi gazetede yayınlanarak olarak yürürlüğe girmiştir. Bu çalışma kapsamında doğrusal elastik olmayan davranış temel alınarak Deprem Bölgelerinde Yapılacak Yapılar Hakkında Yönetmelik esasları çerçevesinde zaman tanım alanında doğrusal elastik olmayan hesap yöntemi kullanılarak mevcut betonarme 15 katlı bir yapı irdelenmiştir. İlk bölümde konu detaylı olarak anlatılmış, amaç ve kapsama değinilmiştir. Ardından ikinci bölümde betonarme ile ilgili genel kavramlara değinilmiştir. Üçüncü bölümde doğrusal olmayan analiz ilkelerinden bahsedilmiştir. Dördüncü bölümde ise performans kavramından bahsedilmiş ve 2007 deprem yönetmeliğindeki yaklaşıma değinilmiştir. Beşinci bölümde zaman tanım alanında doğrusal elastik olmayan hesap yöntemi anlatılmış ve bu çalışmada kullanılacak deprem ivme kayıtlarının belirlenmesi ve kullanımına ait tüm bilgiler detaylı olarak anlatılmıştır. Daha sonra altıncı bölümde sayısal örneğe geçilmiş, mevcut yapının genel bilgileri verilmiş, yükler belirtilmiş, yapılan kabuller ve hesap modelleri gösterilmiştir. Kullanılan program çerçevesinde yapısal modelleme aşaması ve analiz süreci şekiller yardımıyla detaylı olarak anlatılmıştır. Son olarak ise bina hakkında elde edilen bu bilgiler incelenmiş, binanın bu analizler karşısında yapmış olduğu performansı değerlendirilmiş, oluşan hasarın kaynağı hakkında bilgi verilmiş ve sonuçlar yorumlanmıştır. Çalışmanın sonunda ise kullanılan kaynaklar için bir kaynak listesi sunulmuştur.

The high level of damage and loss of life experienced during the last earthquake events indicate the importance of safe and realistic structural design. On the other hand, the recent developments in structural engineering, computer technology and material science enable engineers to predict the real behavior of structural systems under earthquake effects, more accurately. Both linear and non-linear methods are used to analyze the structural systems subjected to earthquake loads. The linear evaluation methods are based on strength and the non-linear evaluation methods are based on deformation and displacement. In the linear theory, it is assumed that the material is linear-elastic and displacements are small, so that the structural analysis can be performed by the conventional linear methods given in the codes. In the non-linear analysis however, the second-order effects and the strength and deformation characteristics of materials beyond linear-elastic limit are taken into account. Nowadays, forced-controlled methods have an important place for assessment of existing structures. In these methods, capacity calculation is done in sections, will be evaluated based on the structure components and system to obtain information of the performance. However, new generation of development studies and computer software may be more realistic and more accurate results for the methods used. Those methods are based of the strain represent the behavior of material facts (non-linear). The design of multi storey reinforced concrete buildings for earthquake action may be efficiently accomplished with the capacity design method. Briefly explained, this method focuses on the establishment of clearly defined plastic hinge zones, proper detailing of these, and the protection of the remaining elastic parts of the building against yielding. For the verification of the structural behavior during an earthquake, there exists however, a need for non-linear dynamic analysis method, as well as for design aid for eccentric and complicated building configurations. For the modeling of the plastic hinge zones, non-linear elements were developed, and implemented as user defined elements into an existing general code. These elements, treating as plastic hinge zones in structural walls, beams, and columns are presented and used in this study. The codes of earthquake are the most significant resource that can be used to build an earthquake-resistant building. According to their geographical location, their geological and sesimic characteristics that apply within the territory and local ground conditions, countries prepare regulations that include the rules, which must be followed during building design. For this purpose, a new Turkish Earthquake Code (TEC) is published in 2007 (Deprem Bölgelerinde Yapılacak Binalar Hakkkında Yönetmelik-DBYBHY) with recent earthquake resistant building design principles. This regulation of the seventh chapter, in earthquake zones available and will be strengthened all the buildings and building structures under seismic effects in assessing the performance will be applied accounting rules, the strengthening in the decisions will be based on principles and strengthening decided buildings strengthen the design principles are included. Developments in structural engineering, computer technology and the material science help engineers to be familiar to the earthquake motions and the effects of earthquake on buildings in a more realistic and accurate way. These developments with the observation of the non-linear behavior of structural systems in an earthquake enable engineers to accomplish designs that are more realistic. In this study, seismic performance of a 15 storey existing reinforced concrete structure is evaluated by the non-linear time history analysis method of Turkish Earthquake Code (TEC) 2007. The present master thesis is composed of seven chapters. The first chapter is designated for the brief explanation of the subject. The aim and the scope of the study is explained in this part. In the next four chapters of this study, non-linear behavior and the analysis are given as the main portion of the study. In this context, non-linear material models are expressed, the stress-strain relationships of various building materials have been analyzed, for the reinforced concrete section, moment-curvature curve properties and interaction surfaces were examined. In addition, quite small information is given about the plastic hinge hypothesis. The sixth chapter is devoted for the numerical investigations. A three dimensional structural model of a 15 storey building is analyzed by a structural analysis program in non-linear time history analysis method given by the TEC 2007. Then the performance level evaluation of the building structure with the non-linear performance approach method of TEC 2007. In this section, firstly an information was given about the existing reinforced structure features which used in analysis model. Loads, seismic zone, material properties, type of structure and a lot of other properties of the building was described. Then for the non-linear analysis, the plastic hinge properties of beams and columns were determined clearly. Shear walls were modeled with non-linear layered shell elements for more accurate results. In this part furthermore, selection and scaling for real earthquake ground motion records are explained briefly. Also in this chapter, important data entry information used for non-linear modeling of the structural components, load analysis and calculated plastic hinge properties and their assigns to the model for performance evaluation of the structural system are presented. The seventh chapter is the final chapter and is devoted to the results, conclusions and recommendations of the study. Main findings, the examination of the results of this study are explained in this chapter. The appendices are given the appendices chapter of this study. In this chapter, data information about the existing reinforced concrete building which used in study, cracked section properties which used in analysis model.
Seismic Performance Evaulation Of 15 Storey Reinforced Concrete Building By Non-linear Time History Analysis
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2015
Thesis (M.Sc.) -- İstanbul Technical University, Instıtute of Science and Technology, 2015
Keywords: Performans; Doğrusal Olmayan; Zaman Tanım Alanı; Performance; Nonlineer; Mander; Time History